An environment for language implementation called SIC - Silva, Mariza Bigonha Andrade da (1996)
SIC is a programming too1 whose purpose is to assist in the developmentpf compilers by"means of a special purpose language, alao cal1ed SIC based on Pascal. SIC possesses facilities to specify the syntax. of programming languages and to associate semantic routines with grammarproductions. It also provides, without loss of eficiency, facilities to imp1ement interactive or batch compilers organized in one or more passes, where each passoperates directIy on the source code, requiring no intermediate language. From the given syntax. specification, the SIC tool produces a compres sed LALR(1) table and a parser containing a language independent error handling and recovery routine. SIC also presents facilities to explicit1y salve LALR(1) conflicts resu1ting from the use of ambiguous grammars. SIC provides compilers in C and Pascal and runs on MS-DOS and WINDOWS.